# Some rules of thumb regarding growth rates 1. The growth rate of a product.

Some quantities are actually products of other quantities. Nominal GDP (call it X), for example, is a product of real GDP (Y) and the GDP deflator (Z). Suppose you were required to find the growth rate of nominal GDP but were given only the growth rate of real GDP and the growth rate of the GDP deflator. In other words, it is known that X = YZ, but you are given only the growth rates of Y and Z and are asked to find the growth rate of X. Let the given growth rates of Y and Z be y and z, respectively. You are asked to find the unknown growth rate of X, call it x. As it turns out, it is true that x ≈ y + z, that is, “The growth rate of a product is approximately equal to the sum of the growth rates of the factors”. For example, if the real GDP grows at 5 percent and the GDP deflator rises at 3 percent, then nominal GDP must have risen by 8 percent or thereabouts, since 0.05 + 0.03 = 0.08. To see why this is so, denote the initial values of the variables as X0, Y0, and Z0. After one period, growing at their respective growth rates, they will have changed respectively to X1 = (1 + x)X0, Y1 = (1 + y)Y0, and Z1 = (1 + z)Z0. We also have the following facts by definition: X0 = Y0Z0 and X1 = Y1Z1. We substitute (1) into the second equation of (2): X0(1 + x) = (1 + y)Y0 (1 + z)Z0 = (1 + y)(1 + z)Y0Z0 = (1 + y)(1 + z)X0 (1 + x) = (1 + y)(1 + z) (1 + x) = 1 + y + z + yz x = y + z + yz x ≈ y + z. (2) (1)

(Use the first equation of (2).) (X0 drops out from both sides.)

This last line is what we wanted to show. The reason we can make the approximation is that yz is usually a small magnitude that can be neglected. For example, if y is 0.05 and z is 0.03, then yz is only 0.0015. So we have the rule: “The growth rate of a product equals the sum of the growth rates of the factors.” This is a rule that works regardless of how many factors there are. 2. The growth rate of a quotient. There is a similar rule that applies to quotients: “The growth rate of a quotient (approximately) equals the growth rate of the numerator minus the growth rate of the denominator.” In other words, if

if tax revenues grow at 15 percent and nominal GDP grows at 11 percent.e.60 percent). it says the relationship between growth rate r and time-to-double T is given by (r ×100)T ≈ 70. if GDP grows only at 4 percent annually. This tends to be a good enough approximation. again consider X1 = X 0 (1 + x ) = (1 + x ) = x= x= Y1 Z1 Y0 (1 + y ) (1 + y ) Y0 (1 + y ) = = X Z0 (1 + z ) (1 + z ) Z0 (1 + z ) 0 (1 + y ) (1 + z ) (1 + y ) !1 (1 + z ) (1 + y ) (1 + z ) ! (1 + z ) (1 + z ) ( y ! z) x= (1 + z ) x " y!z Again this last line is what we wanted to prove. if z is 0.952.1 ! 100) 10 ` By contrast. If. 3. since T= 70 70 = =7 (0.. The “Rule of 70”.There is a rough rule that posits a relationship between the growth rate of something and the time it takes for that thing to double. then the growth in the ratio of taxes to GDP must be approximately 4 percent (although the exact number is more like like 3. since 1/(1 + z) tends to be close to 1 for most purposes. r = 0.5 years for GDP to double. To see why this is so. For example. since then . x ≈ y – z. then it will take about 17. Expressed differently.05. Using this rule of thumb.1). then 1/(1 + z) = 0. The rule states that if something grows at r ×100 percent. which is close to 1. for example.then X = Y/Z. GDP grows at 10 percent (i. then the above says that it should take about 7 years for that GDP to double. then it will take about T = 70/(r ×100) years for it to double.

we set F = 2P.04 ! 100) 4 ` Similarly. so we have PerT = 2P erT = 2.T= 70 70 = = 17. we obtain: (r ×100)T ≈ 70 which is exactly the rule of thumb we had before. then the relationship can be called the “rule of 0.7. . This is just the formula for the natural growth (of anything). We then take logarithms on both sides to obtain: rT = ln 2 = 0.5 (0. Because we are interested in a doubling of P.6931 (You can look up the natural logarithm of 2 using a table or a calculator. Note that if you want to express the growth rate simply as r. Suppose the starting value of some magnitude in question is P and it grows at the rate r for T years. then the above says it will take 20 years for GDP per capita to double. And so on. if we multiply both sides by 100. since then r × T ≈ 0.7”. The mathematical reasoning behind this rule is as follows. the most general description of this relationship is given by the following: PerT = F.7 . Then if we call its future value F. if say GDP per capita grows at 3. Finally.) Note that the right side of the equality is approximately equal to 0. If your hair grows longer by a constant 2 percent annually. then the length of your hair will double in 35 years. where e is the base of natural logarithms.5 percent annually.

y. By definition. Y(t) = Y0eyt. If the initial values are denoted by X0.Appendix The first two rules can also be explained using analysis: 1. So we see that the growth rate x = y + z. and z per period. X(t) = Y0eytZ0ezt = (Y0Z0) e(y + z)t = X0e(y + z)t. then at time t. . Similarly. 2. and therefore x = y – z. Z(t) = Z0ezt. Then X(t) = Y0eyt/ Z0ezt = (Y0 /Z0) e(y – z)t = X0e(y – z)t. Let X = YZ and let each grow respectively at the rate x. we have X(t) = X0ext. Y0. let X = Y/Z. and Z0.

Sign up to vote on this title